2014
DOI: 10.1371/journal.pone.0093599
|View full text |Cite
|
Sign up to set email alerts
|

Maotai Ameliorates Diethylnitrosamine-Initiated Hepatocellular Carcinoma Formation in Mice

Abstract: Consumption of alcohol is closely related to liver disease, such as hepatic fibrosis or even hepatocellular carcinoma (HCC). However, epidemiological and experimental studies indicated that consumption of Maotai, one of the famous liquors in China, exhibits no significant correlation with hepatic fibrosis or cirrhosis as other beverage sources do. This study detected the relationship of Maotai consumption and HCC development in a diethylnitrosamine (DEN)-initiated HCC animal model. DEN was given to mice at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Administration of melatonin to DEN-treated animals indicated that the indole was able to reduce hepatocarcinogenic features in HCC-bearing rats, because it ameliorated histology, and reduced changes in serum enzymes and in the expression of GST-P, a protein considered a marker of hepatocarcinogenesis[ 36 ]. These findings are in accordance with results by different authors that also used DEN as a HCC promoter and tested effects of melatonin or other antioxidants, such as resveratrol, maotai or daffron, in rats [ 24 , 37 40 ] and mice [ 41 ]. Melatonin also prevented DNA damage in DEN-treated animasl, probably due to its capacity to regulate several key genes involved in DNA repairing pathways, such as CEP152 and N4BP2L2 [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Administration of melatonin to DEN-treated animals indicated that the indole was able to reduce hepatocarcinogenic features in HCC-bearing rats, because it ameliorated histology, and reduced changes in serum enzymes and in the expression of GST-P, a protein considered a marker of hepatocarcinogenesis[ 36 ]. These findings are in accordance with results by different authors that also used DEN as a HCC promoter and tested effects of melatonin or other antioxidants, such as resveratrol, maotai or daffron, in rats [ 24 , 37 40 ] and mice [ 41 ]. Melatonin also prevented DNA damage in DEN-treated animasl, probably due to its capacity to regulate several key genes involved in DNA repairing pathways, such as CEP152 and N4BP2L2 [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Its carcinogenesis process goes through liver injury, liver fibrosis, liver cirrhosis and ultimately develops to HCC. HCC animal model induced by DEN is similar to human HCC and represents a better tool for studying human HCC (Iwasa et al, 2010;Yi et al, 2014). ALT, AST and ALP reflect the degree of liver injury, is more reliable as direct indicator (Yim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…80 Sprague-Dawley rats were intraperitoneal administrated with 0.19% Nnitrosodiethylamine DENA (50 mg kg -1 ) every 3 days for a total of 16 weeks to make HCC models (15) .…”
Section: Model Establishment and Experimental Protocolmentioning
confidence: 99%